P069: Prehospital amiodarone use could improve favorable neurological recovery among patients with out-of-hospital shockable cardiac arrest. (15th May 2017) - Kawano, T.; Scheuermeyer, F.X.; Christenson, J.; Stenstrom, R.; Grunau, B.E.
Abstract : Introduction: Amiodarone may be used for shock-refractory ventricular fibrillation (VF) or pulseless ventricular tachycardia (pVT), but the effect of prehospital use upon neurological outcomes still unclear.Methods: A prospective province-wide, population based observational study was conducted from January 2006 to March 2016. Adult emergency medical service-treated non-traumatic OHCA patients who received at least one electric defibrillation were included. Amiodarone was administered to patients with VF/ pVT by paramedics based on their clinical assessment, according to provincial guidelines. The outcome of interest was favorable neurological outcomes to hospital discharge, defined as modified Rankin scale of 3 or less. Multivariable logistic regression was performed to compare the proportion of patients with the primary outcome between amiodarone and non-amiodarone groups, further stratified by the number of electrical defibrillation. In addition, to mitigate the potential selection bias, the same logistic regression was conducted in 1:1 propensity score matched groups adjusting for baseline covariates.Results: Of 3, 374 overall OHCA patients, 915 (27.1%) were managed with amiodarone. In the amiodarone group, 150 / 915 (16.4 %) patients had a favorable neurological outcome, compared to 455/2, 459 (18.5%) in the non-amiodarone group (crude odds ratio [OR] 0.86, 95% CI 0.71 to 1.06). In the multiple logistic regression model, prehospital amiodarone was associated with increased probability of favorable neurological outcomes (adjusted OR 2.11, 95% CI 1.46 to 3.05). With stratification by the number of electrical defibrillation performed, amiodarone treated group showed higher probability of favorable neurological outcomes (1 or 2: adjusted OR 2.71, 95% CI 1.33 to 5.50, 3 and more: adjusted OR 1.67, 95% CI 0.99 to 2.39). Similarly, in 1:1 propensity matched cohort including 882 OHCA patients, the adjusted association persisted (adjusted OR 2.14, 95% CI 1.33 to 3.44).Conclusion: Prehospital administration of amiodarone to non-traumatic OHCA patients was associated with better neurological recovery, especially in those who received fewer electrical defibrillations.